1994
DOI: 10.1083/jcb.127.6.2071
|View full text |Cite
|
Sign up to set email alerts
|

The mucin epiglycanin on TA3/Ha carcinoma cells prevents alpha 6 beta 4-mediated adhesion to laminin and kalinin and E-cadherin-mediated cell-cell interaction.

Abstract: Abstract. TA3/Ha murine mammary carcinoma cells grow in suspension, do not adhere to extracellular matrix molecules, but do adhere to hepatocytes and form liver metastases upon intraportal injection. Recently we showed that the integrin ottfl4 on the TA3/Ha cells is involved in adhesion to hepatocytes. However, despite high cell surface levels of o~6B4, TA3/Ha cells do not adhere to the ot6~4 ligands laminin and kalinin. Here we show that this is due to the mucin epiglycanin that is highly expressed on TA3/Ha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…It has been proposed that mucins interfere with cell-cell or cell-matrix adhesion either through steric hindrance, by masking adhesion molecules and/or by charge repulsion Kemperman et al, 1994;Wesseling et al, 1995;Takeda et al, 2000). In the present report, we provide evidence that in addition to charge repulsion, antiadhesive properties of PC may compete with β1 integrinmediated adhesion.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been proposed that mucins interfere with cell-cell or cell-matrix adhesion either through steric hindrance, by masking adhesion molecules and/or by charge repulsion Kemperman et al, 1994;Wesseling et al, 1995;Takeda et al, 2000). In the present report, we provide evidence that in addition to charge repulsion, antiadhesive properties of PC may compete with β1 integrinmediated adhesion.…”
Section: Discussionsupporting
confidence: 58%
“…Antiadhesive effects have also been demonstrated for other mucins such as episialin, epiglycanin, and leukosialin. The antiadhesive properties of mucins were often revealed by the use of antibodies directed against their extracellular domain (protein core) Cyster and Williams, 1992;DeSmet et al, 1993;Kemperman et al, 1994;Wesseling et al, 1995). Cyster and Williams (1992) suggested that monoclonal antibodies, which recognize the protein core of mucin leukosialin, overcame the repulsion created by the negative charges of this sialoprotein, thus allowing other adhesion molecules to come into play inducing cell-cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, epiglycanin, which is highly expressed on the TA3/Ha mouse mammary tumor cell line, inhibits E-cadherin and integrinmediated adhesion (Kemperman et al, 1994). Similarly, ectopic expression of episialin in adherent cell lines also inhibits E-cadherin and integrin-mediated adhesion (Wesseling et al, 1995(Wesseling et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…For example, epiglycanin, which is expressed at high levels by the mouse mammary tumor cell line TA3/Ha, also inhibits E-cadherin and integrin-mediated adhesion (Kemperman et al, 1994). The expression of yet another sialomucin, the hematopoietic stem cell marker CD34, is reciprocally regulated with the expression of adhesion molecules on endothelium (Delia et al, 1993).…”
Section: Discussionmentioning
confidence: 99%